MXene Films: Scalable Manufacturing of Free‐Standing, Strong Ti3C2Tx MXene Films with Outstanding Conductivity (Adv. Mater. 23/2020). Issue 23 (10th June 2020) - Zhang, Jizhen; Kong, Na; Uzun, Simge; Levitt, Ariana; Seyedin, Shayan; Lynch, Peter A.; Qin, Si; Han, Meikang; Yang, Wenrong; Liu, Jingquan; Wang, Xungai; Gogotsi, Yury; et al.
Abstract : In article number 2001093, Joselito M. Razal and co‐workers demonstrate that ordered domains of additive‐free Ti3 C2 T x MXene liquid crystals can be processed into micrometer‐thin films that do not compromise mechanical properties for electrical conductivity, enabling the development of high‐performance devices and new applications.